Sistem Informasi Perpustakaan Online di Man Kota Solok - Ilham Tri Maulana; Suardinata Suardinata; F Ramadani (Universitas PGRI Semarang, 2018)
Research conducted at the MAN library of Solok city, found the problems of recording and making report book data and borrowing / returning books still using handwritten not stored into the database, as well as students difficulty in finding and knowing the required stock of books, so the required library information system online that can assist in recording, preparing reports and finding and knowing the required stock of books stored in the database. In this research is designed online library information system with PHP programming language and MySQL Database in question to help library MAN city of Solok in data processing book. The method used in this research is SDLC waterfall type and design tool with UML. The results of this study is an application that can provide convenience in recording, reporting and knowing availability of existing stock of books. Officers can make report book data or borrowing / returning more quickly and accurately. Availability of complete book data, making it easier for students to get book information.